Shape and texture analysis of liver cell nuclei in hepatomas by computer aided microscopy. Issue 7 (July 1984) - Jagoe, R; Sowter, C; Slavin, G
Abstract : Nuclei from non-neoplastic hepatocytes and from hepatoma cells have been examined by image analysis techniques which measure size, shape, and texture. There are significant differences in these parameters between malignant and non-neoplastic cells. When values are obtained from multiple cells in a single biopsy, discriminant programs satisfactorily separate benign and malignant tissues. Techniques of image analysis offer an opportunity to quantify the nuclear changes associated with malignancy and may provide an objective basis for tumour grading systems.